Diagnosis and Management of Brain Abscesses in Children - Taslim S. Soetomenggolo; Jimmy Passat; Hardiono D. Pusponegoro; Sofyan Ismael (Paediatrica Indonesiana, 1992)
During 4 years, 20 patients with brain abscesses were hospitalized in the Departement of Child Health, Dr. Cipto Mangunkusumo General Hospital, jakarta. Of those 20 patients 11 were males and 9 were females. The youngest patient was 2 months old and the oldest was 12 years old. The important signs and symptoms in making diagnosis were the sign of injection, increased intracranial pressure, and focal neurological disorders. Laboratory examinations were of little value in establishing the diagnosls of brain abscess. By performing head CT Scan the diagnosis of brain abscess will be confirmed accurately. Of the 20 patients, 15 (75 %) suffered from single abscess and 5 (25 %) suffered from multiple abscesses. The results of treatment by surgical intervention were better than nonsurgical treatment. The high mortallty of the nonsurgical patients was caused by the severity of the disease due to the ignorancy of their parent.